2016
DOI: 10.1210/jc.2016-1472
|View full text |Cite
|
Sign up to set email alerts
|

Study Heterogeneity and Estimation of Prevalence of Primary Aldosteronism: A Systematic Review and Meta-Regression Analysis

Abstract: This study demonstrates that it is pointless to claim low or high prevalence of primary aldosteronism based on published reports. Because of the significant impact of a diagnosis of primary aldosteronism on health care resources and the necessary facilities, our findings urge for a prevalence study whose design takes into account the factors identified in the meta-regression analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
235
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(244 citation statements)
references
References 73 publications
1
235
0
8
Order By: Relevance
“…In particular, 12 studies have been conducted on patients from primary care centers (10,20,21), which represent an apparently unselected hypertensive population, reporting a wide variation in PA prevalence, ranging between 3.2% and 13%. Nevertheless, as suggested by the heterogeneity of the results, these studies could have been biased by the various criteria adopted for patient selection and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 12 studies have been conducted on patients from primary care centers (10,20,21), which represent an apparently unselected hypertensive population, reporting a wide variation in PA prevalence, ranging between 3.2% and 13%. Nevertheless, as suggested by the heterogeneity of the results, these studies could have been biased by the various criteria adopted for patient selection and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Methodological Evaluation of Observational Research (MORE) checklist [21] was used to verify methodological quality and risk of bias. This checklist was designed for quality and bias assessment in incidence or prevalence studies of chronic diseases, and was previously used in several systematic reviews [22][23][24][25][26][27][28]. Two authors (M.C.B., H.F.L.)…”
Section: Data Extractionmentioning
confidence: 99%
“…1 The prevalence of primary aldosteronism is reported as 5% in the general hypertensive population, 2 increasing to 10% in referred populations and 15–20% in patients with treatment-resistant hypertension, 3 although estimates vary widely. 4 Several studies have shown a higher prevalence of cardiovascular and cerebrovascular morbidity and mortality in patients with primary aldosteronism than in patients with primary hypertension matched for age, sex, and blood pressure, 58 with resolution of excess risk after surgical or specific medical treatment. 910 As such, early diagnosis and appropriate treatment of primary aldosteronism are essential to minimise the increased risk associated with this disorder.…”
Section: Introductionmentioning
confidence: 99%